MnO6 octahedron in transition metal oxide for electrochemical energy conversion and storage - Wei, Chao (2016)
Climate changes and the scarcity of fossil fuels have stimulated extensive studies on electrochemical devices for energy storage and conversion. Among various earth-abundant electrode materials, MnO6 octahedron-based metal oxides have emerged as one of the most promising candidates, and thus requiring a better understanding on the relationship between the physical properties of MnO6 octahedron and the corresponding electrochemical performance. A better understanding of Mn gives benefits to rational design of electrode materials for supercapacitor and oxygen electrocatalysis devices. This dissertation firstly investigates the influence of particle size on ORR (oxygen reduction reaction). Without tuning the specific activity, a high mass activity is achieved by nano-engineering MnO6 octahedron into uniform-sized MnO2 nanoflakes, which provides more electrochemical-active sites. Second, the uniform-sized MnO2 nanoflakes serve as the standard active component of pseudocapacitor to understand the interplay between MnO6 octahedrons and various carbon supports, i.e., AB (acetylene black), rGO (reduced-graphene oxide) and CNTs (carbon nanotubes). MnO6 octahedrons supported on rGO can be fully utilized at slow rate and gives the highest capacitance; while, CNTs and AB displays better energy storage capability at high scan rates. Third, MnO6 octahedron is put in the crystal environment of spinel oxides to reveal the role of MnO6 octahedron in pseudocapacitive performance. By employing spinel ferrites XFe2O4 (X = Mn, Fe, Co, Ni) as the model material, we demonstrate the superior ability of MnO6 octahedron to change valence state and thus MnFe2O4 gives the highest pseudocapacitance. Forth, efforts are devoted to unveil the role of MnO6 octahedron in oxygen electrocatalysis. The electronic structure of MnCo2O4 is tuned via varying the heat treatment temperature and the resulting ORR and OER (oxygen evolution reaction) performance are correlated with valence state and cation distribution. It is proven that the valence state of Mn in MnO6 octahedron and the fraction of Mn that occupies in the octahedral site govern the ORR/OER activity. The universality of the as-revealed descriptor of MnCo2O4 is further validated by extending it to describe the ORR/OER at transition metal spinels.